BMY 28100, a new oral cephalosporin. - Leitner, F (1987)
BMY 28100, a new oral cephalosporin with a (Z)-propenyl side chain at the 3 position and a p-hydroxyphenylglycyl substituent at the 7 position, was evaluated in comparison with cefaclor and cephalexin and, when appropriate, ampicillin and vancomycin. In vitro, BMY 28100 was more active than the reference cephalosporins against streptococci, Staphylococcus aureus, Staphylococcus epidermidis, Listeria monocytogenes, Haemophilus influenzae, Propionibacterium acnes, Clostridium perfringens, and Clostridium difficile. BMY 28100 was comparable to cefaclor and more active than cephalexin against Staphylococcus saprophyticus and ampicillin-susceptible strains of Branhamella catarrhalis; but against ampicillin-resistant strains of B. catarrhalis, BMY 28100 was comparable to cephalexin and more active than cefaclor. Against Neisseria gonorrhoeae, BMY 28100 was comparable to cephalexin, but less active than cefaclor. Members of the family Enterobacteriaceae overall were equally susceptible to BMY 28100 and cefaclor but were less susceptible to cephalexin. In human serum, BMY 28100 was 45% protein bound. After an oral dose to mice, 82% of the drug was recovered in urine. The oral therapeutic efficacy of BMY 28100 in systemically infected mice reflected its activity in vitro.